Etnoekologi Masyarakat Adat Tepra Pada Pegunungan Cycloop Papua - Richard Kalilago; Maria F Suwae (CENDERAWASIH: Jurnal Antropologi Papua, 2021)
The purpose of this article is to describe and analyze in depth the ethnoecology of the Tepra indigenous people in the Cycloop Mountains. The Tepra Indigenous People are from the Ethno Ecology aspect which includes the community's ecological view of the surrounding natural environment, the interaction of the Tepra with natural resources in traditional zones in the context of managing and utilizing limited natural resources. The research location is in Yongsu Desoyo village, Ravenirara district, Yewena village, Dormena, Wambena, Yepase and Tablasupa village, Depapre district. Data collection techniques were carried out by direct observation in the field, open interviews, and to focus group discussions (FGD). The local power summer management in the Tepra community is described descriptively using a spatial approach (spatial approach). The results of the research show that traditional community knowledge about the environment is reflected in the form of land use and utilization and its management system.